The Effect of a Combination of Marsilea crenata and Moringa oleifera Leaves Ethanol Extract on Follicles and Oocytes Diameter of Goat: In Vitro Study - Putranto, Septiawan; Widhaningrum, Siska Nanda; Rahayu, Sri; Ciptadi, Gatot (Biotropika: Journal of Tropical Biology, 2023)
Marsilea crenata and Moringa oleifera are herbal plants widely used in various alternative medicines due to their antioxidants and estrogenic activity. The current study investigated the effect of a combination M. crenata and M. oleifera leaves ethanol extract on the growth of follicles and oocytes of goats in vitro. Twenty-four antral follicles of Ettawa Crossbred Goat (Capra aegagrus hircus) were randomly grouped into four groups: K (control, without extract treatment), D1 (21.6 microgram/mL of M. crenata ethanol extract), D2 (21.6 microgram/mL of M. oleifera leaves ethanol extract), and D3 (combination of M. crenata and M. oleifera leaves ethanol extract at the dose of 21.6 microgram/mL). The follicle diameter was measured on days 0, 3, and 6 of culture, while the oocyte diameter was only examined on day 6. After being treated with the combination of M. crenata and M. oleifera leaves ethanol extract (D3), the diameter of the ovarian follicles increased significantly (p<0.05) from day-0 to day-6. D3 group also greatly enhanced estrogen levels in the follicular fluid of goats compared to a single extract. However, the diameter of the oocyte was not significantly increased after being treated with a single or combination of both extracts. Therefore, this study suggested that combination of M. crenata and M. oleifera leaves ethanol extract can be used as phytoestrogen to enhance follicular growth and estrogen levels.